Effect of in ovo injection of raffinose on growth performance and gut health parameters of broiler chicken - Berrocoso, J. D. (Poult Sci, 2017)
The effects of in ovo injection of raffinose (RFO) as a prebiotic on growth performance, relative weight of proventriculus, gizzard, drumstick and breast muscles, and ileum mucosa morphology were examined in Cobb 500 broilers. A total of 240 fertilized eggs were divided into 4 groups: a non-injected with intact shell and 3 levels of RFO solution (1.5, 3.0, and 4.5 mg in 0.2 mL of an aqueous diluents). The RFO solution was injected into the air sac on d 12 of incubation. In total 144 birds were fed a standard diet and management and sacrificed at d 21 post hatch for collection of samples. Total RNA was extracted from the small intestine, and RT-qPCR was performed to quantify mRNA levels of marker genes of immune cells. Injection of RFO had no significant effect (P > 0.05) on d one body weight of chicks. On d 21, the relative weight of the proventriculus, drumstick, breast, and gizzard was not affected (P > 0.05) by RFO. On hatch d, the villus height increased linearly (P < 0.01) with an increasing dose of RFO. Also, an increasing dose of RFO increased the villus height and villus height:crypt depth ratio (P < 0.05) but did not affect the crypt depth on d 21. The expression levels of CD3 and chB6, which are T cell and B cell marker genes, respectively, were significantly enhanced by high dose RFO (4.5 mg). In conclusion, although an increasing dose of RFO in ovo injection did not significantly influence growth performance or slaughter yield of broilers, RFO has the potential of enhancing ileum mucosa morphology and improving immunity in the small intestine, which are indicators of improved gut health.